Negotiated Readiness: A Phenomenological Study of PAI Teachers' Sense-Making of AI-Gamification in Qur'anic Learning - Nursani Awal Artha Nugraha; Mokh. Iman Firmansyah; Risris Hari Nugraha (Institut Agama Islam An-Nawawi Purworejo, 2026)
Research on teacher readiness for AI-gamification in Islamic education has predominantly treated readiness as a static, measurable condition, systematically misreading principled pedagogical conditionality as technological resistance. This study reconceptualises readiness as an active negotiation process by investigating how five lower-secondary Islamic Religious Education (PAI) teachers in Bandung and Cimahi, Indonesia, make sense of AI-gamification as a pedagogical possibility in Qur'anic learning. Employing secondary qualitative analysis through Interpretative Phenomenological Analysis (IPA; J. A. Smith et al., 2009), semi-structured interview transcripts were analysed idiographically before cross-case patterns were constructed via a four-stage double hermeneutic procedure. Analysis generated five superordinate themes: readiness as an ongoing negotiation trajectory; Qur'anic pedagogical identity as an actively maintained boundary; adoption conditions as expressions of pedagogical competence rather than resistance; the institutional ecosystem as a negotiation field beyond teachers' control; and teachers as moral agents directing technology. These themes converge to suggest that what instrumentalist frameworks read as adoption barriers may be more productively understood as epistemic maturity. From this foundation, the study proposes the Negotiated Readiness framework as an epistemological complement to TPACK, TAM, and Organisational Readiness Theory, articulated through four dimensions: temporal processualism, identity-embeddedness, conditional competence, and ecosystemic boundedness. Findings call for a fundamental reorientation of PAI teacher professional development — from generic vocational instruction towards domain-specific, negotiation-aware capacity building.